PENGARUH RASIO KEUANGAN TERHADAP NILAI PERUSAHAAN SUB SEKTOR BANK BUMN DAN SWASTA - Alya Azka Nadzifa; Dewa Putra Krishna Mahardika (Jurnal Proaksi, 2023)
Firm value is indeed an important measure of company performance that reflects both its current situation and future opportunities. It represents the attractiveness of a company's shares to investors in the market, particularly for publicly traded companies. Business companies that have gone public will offer shares to investors in the hope of obtaining large shares from the market. In this research investigated the impact of loan-to-deposit ratio (LDR), net interest margin (NIM), and non-performing loans (NPL) on firm value. By employing descriptive statistical data analysis and panel data regression using the Eviews 12 application, you aimed to analyze the relationships between these variables. The population of the study consisted of bank sub-sector companies listed on the IDX for the period 2019-2021, excluding regional commercial banks and Islamic banks. Purposive sampling was used, resulting in 111 samples. The simultaneous results of your study indicate that NPL, LDR, and NIM collectively have an effect on firm value. This implies that these three variables, when considered together, contribute to changes in firm value among the selected samples.